Kreea - Lim, Jean Angelica O.
God, being almighty, can do anything, everything, that is, except to contradict himself. And yet he has created a contradiction --- man. A human soul, an endless being locked in a finite body. He has created Paradise, a heaven on earth. Is Adam a figment of His divine imagination, the projection of a childhood that He cannot have? In Paradise God provided everything to make Adam happy. It is as if it is forbidden to be sad in Paradise. There is, however, one rule: don't eat the apple. What is the real message behind that rule? It could not have been all about one silly apple. Is it really about Obedience? What for? God does not have to prove this superiority. Nor does He need anybody to serve Him. What did he give Adam a free will for? Traditional thinking would consider Adam's exercise of his free will and his loss of Paradise as ignominy-the Original Sin. However, this could also be seen as a man's first act of independent thinking, the first exercise of man's imagination. It represents rather than resulted in, loss of innocence-an awakening. I don't think Adam lost Paradise. He probably simply left it, as one leaves his childhood when he comes of age. Maybe there was no Paradise in the first place but rather a place where children can play and be happy until they wake up one day to find themselves thinking of things other than fun and games. The playground is still there but the innocence that was Paradise, is gone. This is what my thesis is about. A yearning to relive those happy, innocent and carefree childhood years that provided the perfect atmosphere for my developing imagination and first act of creativity. "Kreea" is an eight-minute animation feature that paints a picture of a child's perfect fantasy world and its undoing brought about by the intrusion of reality. The story is actually an allegory that I based from my own childhood fantasies and life experience. For this lyrical style, I believe it is only through animation that I can freely express the unlimited scope of the child's imagination. In this manner, I also free myself from the structured and inflexible dictates of real life.